The Effect of Cake Application Toward Students Speaking Mastery (A Quasi-Experimental Study) - Elpita Sari; Ferri Susanto; Yashori Revola (Journal of Innovation in Teaching and Instructional Media, 2026)
This quasi-experimental study examined the effect of the Cake application on the English-speaking proficiency of tenth-grade students at SMA Negeri 04 Seluma in the 2024/2025 academic year. The study involved 60 students from two intact classes, with one class assigned as the experimental group taught using the Cake application and the other as the control group taught through conventional instructional methods. Students’ speaking ability was measured through pre-test and post-test assessments using a structured speaking test scored with a validated analytic rubric assessing fluency, pronunciation, vocabulary, and grammatical accuracy. The data were analyzed using descriptive statistics and inferential analysis. The results showed that the experimental group demonstrated a substantial improvement in speaking proficiency, with the mean score increasing from 57.06 to 74.79, which was significantly higher than the improvement observed in the control group from 53.00 to 62.23. An independent samples t-test revealed a statistically significant difference between the post-test scores of the two groups (t (58) = 3.79, p < .001). These findings indicate that the Cake application is effective in improving students’ English-speaking proficiency and suggests that mobile-assisted language learning applications can serve as effective supplementary tools for enhancing speaking skills in senior high school EFL contexts, particularly in rural educational settings.